O Centro de Mídia Independente: a política e a estética - Nascimento, Thayane Cazallas do (Universidade do Vale do Rio dos Sinos, 2013)
This paper seeks to understand a political group of independent media that was created in 1999 and is called Indymedia - IMC. The research is dedicated to related themes such as the Internet's virtual network, context in which the main theme develops: the politics and aesthetics (in the community sense) of the IMC group. The research counts with the imbrications of the global citizen movement, in the city of Seattle as the place where "everything" started, as a place of inspiration to the first IMC collective, and latter the first collective, and in a great speed, consolidates more collectives in many countries. Considering the changes in the core of the political group of media, we dedicated a reflexion based on the "first times", where it can follow the relation between the first period and it's notable differences of activities, the in which are equivalent to the transformations of communications, form the access of the network in the contemporary society. The research counts with a interview with the ex-voluntary of the Porto Alegre-RS collective, dedicated to bring together the activities and the participation of the activists with in the collective. The research goes through the concept of network, cyberspace, Internet culture and collectives.
Keywords: Redes; Ciberespaço; Coletivo; Contemporaneidade; Network; Cyberspace; Collective; Contemporaneity; ACCNPQ::Ciências Humanas::Sociologia